2017
DOI: 10.1037/neu0000335
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides are negatively correlated with cognitive function in nondemented aging adults.

Abstract: Objective Vascular risk factors like hyperlipidemia may adversely affect brain function. We hypothesized that increased serum triglycerides are associated with decreased executive function and memory in non-demented elderly subjects. We also researched possible vascular mediators and white matter microstructure as assessed with diffusion tensor imaging (DTI). Design/Methods Participants were 251 non-demented elderly adults (54% male) with a mean age of 78 (SD=6.4; range: 62–94) years and a mean education of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 41 publications
3
24
1
Order By: Relevance
“…We also found significantly higher plasma TG levels in VaD subjects. Numerous studies have indicated a relationship between high TG levels and poor cognitive performance in diabetic patients [48] , [49] . A similar finding was reported in the Honolulu-Asia Aging Study in which a 1 SD increase in TG levels during midlife significantly increased the risk of dementia a quarter of a decade later [50] .…”
Section: Discussionmentioning
confidence: 99%
“…We also found significantly higher plasma TG levels in VaD subjects. Numerous studies have indicated a relationship between high TG levels and poor cognitive performance in diabetic patients [48] , [49] . A similar finding was reported in the Honolulu-Asia Aging Study in which a 1 SD increase in TG levels during midlife significantly increased the risk of dementia a quarter of a decade later [50] .…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available kits (LABTEST, Brazil) were used for these assays. Triglycerides were assessed because their levels are inversely correlated with executive function in non-demented elderly adults after controlling for age, vascular risk factors, and fiber tract integrity (20).…”
Section: Methodsmentioning
confidence: 99%
“…For example, while TC and LDL-C did not contribute to cognitive impairment for Hispanics/Latinos of Caribbean background (Reitz et al, 2008), a Brazilian study reported associations between lower HDL-C and lower declarative and working memory (Ihle et al, 2017). A study of a heterogeneous group of older adults fluent in English reported a negative association between TG levels and executive functioning but not memory (Parthasarathy et al, 2017). These studies lay the foundation for a comprehensive investigation of the relationship between lipid levels (i.e., TC, LDL-C, HDL-C, and TG) and cognition within a large cohort study of Hispanics/Latinos from multiple backgrounds.…”
Section: Introductionmentioning
confidence: 98%
“…All but one (Del Brutto et al, 2016) found that individual lipid levels contributed to these cognitive profiles. More directed studies either including (Reitz et al, 2008) or exclusively composed of Hispanics/Latinos (Ihle et al, 2017;Parthasarathy et al, 2017) reported differing results based on the lipid level and/or background studied. For example, while TC and LDL-C did not contribute to cognitive impairment for Hispanics/Latinos of Caribbean background (Reitz et al, 2008), a Brazilian study reported associations between lower HDL-C and lower declarative and working memory (Ihle et al, 2017).…”
Section: Introductionmentioning
confidence: 99%